Evaluating the dilution of sodium hypochlorite in Family Health Strategy - Antunes, Juliana Teixeira; Carvalho Mendes, Josianne Fernanda; Alves, Carolina dos Reis (Journal of Health Care, 2017)
Introduction: Sodium hypochlorite is a chemical compound widely used in Family Health Strategy (FHS) for the disinfection of semicritical articles, such as inhalation masks. Objectives: This research sought to investigate, in terms of dilution and conservation, the sodium hypochlorite solutions used in FHS of a municipality. Materials and methods: This is a cross-sectional study with quantitative-descriptive-analytical field research. The data were collected through a semi-structured questionnaire applied to seven health units FHS. The descriptive analysis of the responses occurred through the interpretation of the frequencies and measures of central tendency and dispersion generated by the program Epi Info 3.5.3. Results: It was noticed that sodium hypochlorite dilution is not performed as recommended in the literature. In the FHS there was variation regarding the amount of hypochlorite dispensed to compose the disinfectant solution and the immersion time of the inhaler kits in the solution. Conclusions: The research results show a need to standardize routines and implement the permanent education of the professionals responsible for reprocessing the articles in the FHS.